DECLARATIVE AND PROCEDURAL KNOWLEDGE IN TEACHING GRAMMAR - Bambang Suroso (University of Muhammadiyah Purwokerto, 2010)
When one has to teach a language, he should possess a vlew of whatlanguages. One possibility is to view language as a skill. Thereforelanguage learning is comparable to other types of cognitive skillacquisition. ln this case, there is a need for us to understand theconcept of declarative and procedural knowledge. This is similar tothat of knowledge about and knowledge how or knowledge and control(Bialystok, in Johnson, 1994), competence and performance, and usageand use. The first of those terms refers to factual knowledge of alanguage such as grammar, vocabulary, pronunciation etc., and thelatter to the actual use of the knowledge in real act of communicationsuch as in speaking, reading, listening and writing. The problem ishow these two knowledge can be developed. This paper is inspired byKeith Johnson whose Teaching Declarative and Procedural knowledgesuggest that the strategy to develop the knowledge correspond to whatis commonly called learning and acquisition.